2016
DOI: 10.1186/s12929-016-0282-z
|View full text |Cite
|
Sign up to set email alerts
|

Cellular effects induced by 17-β-estradiol to reduce the survival of renal cell carcinoma cells

Abstract: BackgroundRenal cell carcinoma (RCC) is an adult malignancy with 2:1 men-to-women ratio, which implies the possible role of sex hormones in RCC carcinogenesis. One of the predominant sex hormones in women before menopause, 17-β-estradiol (or E2), may regulate RCC growth by cellular mechanisms that are still not fully understood.MethodsThe expression levels of E2 receptors (ER1 and ER2) were determined in different RCC cell lines. The DNA damage response induced by E2 was determined by a DNA double-strand break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…10 μM, for more than 6 months (16), and confirmed that SunR 786-O cells showed less growth inhibition by sunitinib than PAR cells (p<0.01) (Figure 1A). In agreement with previous studies (8,9,13), estrogen repressed growth of both PAR and SunR 786-O cells at relatively high concentrations (1 to 5 μM) (Figure 1B).…”
Section: Gper1 Agonist G-1 Inhibited Cell Growth Of Both Par Andsupporting
confidence: 93%
See 1 more Smart Citation
“…10 μM, for more than 6 months (16), and confirmed that SunR 786-O cells showed less growth inhibition by sunitinib than PAR cells (p<0.01) (Figure 1A). In agreement with previous studies (8,9,13), estrogen repressed growth of both PAR and SunR 786-O cells at relatively high concentrations (1 to 5 μM) (Figure 1B).…”
Section: Gper1 Agonist G-1 Inhibited Cell Growth Of Both Par Andsupporting
confidence: 93%
“…It has been shown that estrogen represses RCC cell growth via classical estrogen receptors (8,9), and perturbs sunitinib resistance in in vitro RCC cell culture (13). The role of nonclassical estrogen receptor GPER1 in RCC physiology, however, is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, sex hormones have been shown to have a certain effect on the development and progression of RCC 26 , 27 . However, the effect of sex hormone in Xp11.2 tRCCs was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In RCC, the level and frequency of ER expression is highly variable, with a higher frequency of ERβ than ERα, and there are very limited and contrasting data concerning the role of estrogenic signals in the tumorigenesis and development of RCC [52,[70][71][72][73]. Previous studies demonstrated that estrogen, through ERβ signaling, suppressed the proliferation, migration and invasion of RCC cells and increased RCC apoptosis [74][75][76]. Analysis of the molecular mechanisms revealed that estrogen reduced the expression of downstream genes, such as AKT, extracellular signal-regulated kinase (ERK) and Janus kinase (JAK) signaling pathways and increased the apoptotic genes (BH3 interactingdomain death agonist (Bid), Caspase-3, Caspase-8 and Caspase-9), through ERβ activation, suggesting that this receptor could have an inhibitory effect in RCC [75,76].…”
Section: The Estrogen Signalling Axismentioning
confidence: 99%